Populasi dan Karakteristik Habitat Tarsius (Cephalopachus bancanus borneanus) di Punggualas, Taman Nasional Sebangau: Population and Habitat Characteristics of Tarsier (Cephalopachus bancanus borneanus) in Punggualas, Sebangau National Park - Robby Octavianus (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2020)
Tarsier (Cephalopachus bancanus borneanus) is one of the endemic primates in Kalimantan. IUCN (International Union for the Conservation of Nature and Natural Resources) has established the conservation status of Cephalopachus bancanus borneanus as a vulnerable primate. This research was conducted in the Punggualas area, Sebangau National Park, from June to August 2019. The data collected was the number and distribution of tarsier population along with the composition and structure of vegetation. This study revealed that tarsiers in Punggualas have a tendency to live solitary. A total of 6 tarsier individuals were found in an area of ??4 km2, with a total length of 22 km of transects. The population in the scope of the study area is 23 individuals who occupy an area of ??4 km2 with a population density of 5,682 individuals / km2. The density of vegetation in Punggualas reaches 1179 individuals per hectare at the sapling level, where this area is a suitable habitat for shelter, locomoting, and as sleeping site for Tarsiers.